2000
DOI: 10.1016/s0550-3213(99)00533-7
|View full text |Cite
|
Sign up to set email alerts
|

The basis of the physical Hilbert space of lattice gauge theories

Abstract: Non-linear Fourier analysis on compact groups is used to construct an orthonormal basis of the physical (gauge invariant) Hilbert space of Hamiltonian lattice gauge theories. In particular, the matrix elements of the Hamiltonian operator involved are explicitly computed. Finally, some applications and possible developments of the formalism are discussed.CPT-99/P.3856 University of Parma Preprint UPRF-99-09 xxx-archive: hep-lat/9906036.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 20 publications
6
46
0
Order By: Relevance
“…In such a setup Gauss's law on the states is explicitly resolved with the help of the gauge constraint, without any need to construct the physical Hilbert space explicitly [5]. The results obtained [6] agree with the Gribov-Zwanziger confinement scenario [7][8][9] and with the existence of a confining potential driven by topological excitations [10][11][12].…”
Section: Introductionsupporting
confidence: 63%
“…In such a setup Gauss's law on the states is explicitly resolved with the help of the gauge constraint, without any need to construct the physical Hilbert space explicitly [5]. The results obtained [6] agree with the Gribov-Zwanziger confinement scenario [7][8][9] and with the existence of a confining potential driven by topological excitations [10][11][12].…”
Section: Introductionsupporting
confidence: 63%
“…In this work, the angular momentum basis [45,49,50] is utilized, made computationally feasible on quantum devices by exploiting the local gauge symmetry to remove the angular momentum alignment variables. Time evolution of a one-dimensional string of two SU(2) plaquettes is then implemented on IBM's Tokyo [93] quantum device with employed error mitigation techniques.…”
mentioning
confidence: 99%
“…This can be generalized to non-Abelian gauge symmetry. For example, Burgio et al [51] have shown how to construct a gauge invariant Hilbert space for the gauge group SU(2). irreducible representation characterized by index (set) {ν} is given by a matrix…”
Section: Discussionmentioning
confidence: 99%